The Dependence between Hourly Prices and Trading Volume - Jain, Prem C.; Joh, Gun-Ho (Journal of Financial and Quantitative Analysis, 1988)
This study provides evidence on joint characteristics of hourly common stock trading volume and returns on the New York Stock Exchange. Average volume traded shows significant differences across trading hours of the day and across days of the week. Average returns differ across hours of the day, and, to some extent, across days of the week. There is a strong contemporaneous relation between trading volume and returns and also a relation between trading volume and returns lagged up to four hours. Furthermore, the trading volume-returns relation is steeper for positive returns than for nonpositive returns.